Budaya Patriarki dan Lokalisasi Norma Pemberantasan Perdagangan Manusia di Indonesia - Bastari, Gema Ramadhan (Global: Jurnal Politik Internasional, 2018)
This paper will discuss about the problem surrounding human trafficking eradication in Indonesia. In general, the effort to eradicate human trafficking in Indonesia has been focusing too much on enforcing criminal law and restricting immigration instead of protecting and preventing the victim of trafficking. In order to explain why it happened, this paper will use Amitav Acharya’s theory on norm localization which provides a framework to assume that the norm of human trafficking eradication in Indonesia has been appropriated by certain contradicting value. By using the theory, this paper finds that the norm of human trafficking eradication promoted by Palermo Protocol is directly against patriarchal culture, thus the culture has an interest to localize the norm. This paper concludes that the localization of human trafficking eradication norm by patriarchal culture in Indonesia has removed the value of human security in favor of state security.